Rotating hinge knee as a means of limb salvage in a patient operated on five times for periprosthetic joint infection: from despairs of darkness to lights of joy! - Shah, Vikram; Pachore, Javahir; Patil, Jayesh; Gujjar, Pranay; Sinha, Amit Kumar (International Journal of Research in Orthopaedics, 2023)
The demand for revision knee arthroplasty is increasing daily with the increase in the number of patients undergoing primary knee arthroplasty. The aim of revision arthroplasty therefore should be the restoration of the mechanical alignment of the limb with the restoration of joint line and biomechanics and these goals should be accomplished with the least possible use of constrained implants which otherwise depends on the degree of bone defects and integrity of collateral ligaments. We have hereby reported a case of a 51-year-old lady operated on five times before who was financially drained, mentally and psychologically depressed with the patient and her relative’s considering amputation of the limb as a last resort!